Cyanidin 3-O-Glucoside Induces the Apoptosis in the Osteosarcoma Cells through Upregulation of the PPARγ and P21: An In Vitro Study - Atashi, Hesam A.; Arani, Hamid Z.; Shekarriz, Amirhossein; Nazari, Hamidreza; Zabolian, Amirhossein; Rakhshan, Rasul; Olya, Maedeh (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Osteosarcoma (OS) is known as the malignant tumors in the bone. Cyanidin 3-OGlucoside (C3G) has a potential to induce the apoptotic cell death in different cancer cells; however, the mechanisms of action for C3G have not been clarified yet. Objective: In this study, the apoptotic effects of C3G on three different osteosarcoma cell lines including Saso-2, MG-63, and G-292 (clone A141B1) were investigated. Methodology: The 24-hr IC50 of C3G for Saso-2, G-292, and MG-63 cells was evaluated by the MTT assay. Apoptosis induction in these cell lines after treatment with the C3G was approved by the Annexin V/PI flow cytometry. Changes at the mRNA expression level of PPARγ, P21, Bax, and Bcl-xl genes were investigated by real-time Polymerase Chain Reaction (PCR) technique, and P21 expression was further confirmed by the western blotting. Results: The MTT assay results demonstrated that the 24-hr IC50 of C3G was equal to 110μg/ml for Saso-2 and G-292 cells while it was about 140μg/ml for the MG-63 cells. The results of real-time PCR clearly showed that treatment of the cells with 24hrs IC50 of C3G caused the upregulation of PPARγ, P21, and Bax genes. Moreover, western blot analysis confirmed that P21 protein overexpressed endogenously after treatment of the cells with the C3G, and it was more upregulated in the MG-63 cells compared to the other cell lines. Conclusion: According to the findings of the study, the C3G is a novel anti-osteosarcoma agent with the ability to induce the apoptosis in different osteosarcoma cells through upregulation of the PPARγ and P21 genes.
Keywords: MTT